Homicide by unusual‐edged weapons: Forensic considerations of two cases. Issue 1 (28th September 2020) - Karray, Narjes; Dedouit, Fabrice; Dubois, Clarisse; Savall, Frederic; Telmon, Norbert
Abstract: Homicide by stab wound is common worldwide. However, the use of unusual edged weapons is rarely reported in the forensic literature. Here, we report two cases of homicide involving a Japanese sword, or katana, and a sickle. Both of these weapons can create either stab or incised wounds with some particularities. In our cases, characteristics of the external wounds, internal injuries, and the depth of penetration raised the possibility of an unusual weapon. Meticulous forensic examination of these injuries (morphological characteristics, depth of penetration, trajectories, and cut marks in the bone) may allow the forensic expert to determine the type of weapon used.